2014
DOI: 10.1007/s11010-014-2233-x
|View full text |Cite
|
Sign up to set email alerts
|

Low glucose transporter SLC2A5-inhibited human normal adjacent lung adenocarcinoma cytoplasmic pro-B cell development mechanism network

Abstract: Solute carrier family 2 (facilitated glucose/fructose transporter) member 5 (SLC2A5)-inhibited seven different molecular Pearson mutual-positive-correlation networks constructed by 24 overlapping molecules from 368 GRNInfer and 34 Pearson under SLC2A5 CC ≤-0.25 in low human normal adjacent tissues were compared with high lung adenocarcinoma. Based on GO, KEGG, GenMAPP, BioCarta, and disease databases, our result showed that low SLC2A5-inhibited network included Golgi apparatus of AP1M2_1; cell cycle of CUL7, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Enrichment analysis revealed that SAC3D1 and 4 other SAC3D1-related genes (CDK1, CCNB1, CCNB2 and CDC20) are important for GC development via the cell cycle pathway. Numerous studies have reported the overexpression of SAC3D1 in several types of cancer, including hepatocellular carcinoma (11), colon cancer (12) and lung adenocarcinoma (13). Recent studies have assessed the prognostic value of SAC3D1 using GEO, the Cancer Genome Atlas and International Cancer Genome Consortium and suggested that SAC3D1 may be a credible prognosis-related biomarker for hepatocellular carcinoma (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enrichment analysis revealed that SAC3D1 and 4 other SAC3D1-related genes (CDK1, CCNB1, CCNB2 and CDC20) are important for GC development via the cell cycle pathway. Numerous studies have reported the overexpression of SAC3D1 in several types of cancer, including hepatocellular carcinoma (11), colon cancer (12) and lung adenocarcinoma (13). Recent studies have assessed the prognostic value of SAC3D1 using GEO, the Cancer Genome Atlas and International Cancer Genome Consortium and suggested that SAC3D1 may be a credible prognosis-related biomarker for hepatocellular carcinoma (11).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of SAC3D1 has also been demonstrated in colon cancer (12). You et al reported that SAC3D1 was associated with SLC2A5-inhibited adjacent lung adenocarcinoma cytoplasmic pro-B cell progression (13). However, the role and molecular mechanisms of action of SAC3D1 in GC have not…”
Section: Introductionmentioning
confidence: 99%
“…The protein encoded by SLC2A5 is a fructose transporter responsible for fructose uptake,26 and the protein encoded by CACNA1D is the alpha-1D subunit of calcium channel 27. Enhanced growth and proliferation of tumor cells place increased demand for nutrients for the synthesis of DNA and protein 28.…”
Section: Discussionmentioning
confidence: 99%
“…Con, human normal adjacent tissues; Ex, lung adenocarcinoma; Act, activation Immunol Res out interactive inflammation immune-induced transcription-dependent apoptosis using SAM [7][8][9][10][11][12]. The GSE7670 raw microarray data were processed by log base 2, two classes were paired, and minimum fold change C2 selected (the false-discovery rate 0 %) [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression values of BIK-activatory different molecules were computed in low normal adjacent tissues compared with the corresponding high lung adenocarcinoma by AVERAGE and STDEV [13,14].…”
Section: Methodsmentioning
confidence: 99%